The C2-domain protein QUIRKY and the receptor-like kinase STRUBBELIG localize to plasmodesmata and mediate tissue morphogenesis in Arabidopsis thaliana - Vaddepalli, Ponduranga Vara Prasad; Hillmer, Stefan; Robinson, David G. (Development, 2014)
Tissue morphogenesis in plants requires communication between cells, a process involving the trafficking of molecules through plasmodesmata (PD). PD conductivity is regulated by endogenous and exogenous signals. However, the underlying signaling mechanisms remain enigmatic. In Arabidopsis, signal transduction mediated by the receptor-like kinase STRUBBELIG (SUB) contributes to inter-cell layer signaling during tissue morphogenesis. Previous analysis has revealed that SUB acts non-cell-autonomously suggesting that SUB controls tissue morphogenesis by participating in the formation or propagation of a downstream mobile signal. A genetic screen identified QUIRKY (QKY), encoding a predicted membrane-anchored C2-domain protein, as a component of SUB signaling. Here, we provide further insight into the role of QKY in this process. We show that like SUB, QKY exhibits non-cell-autonomy when expressed in a tissue-specific manner and that non-autonomy of QKY extends across several cells. In addition, we report on localization studies indicating that QKY and SUB localize to PD but independently of each other. FRET-FLIM analysis suggests that SUB and QKY are in close contact at PD in vivo. We propose a model where SUB and QKY interact at PD to promote tissue morphogenesis, thereby linking RLK-dependent signal transduction and intercellular communication mediated by PD.